Understanding Filipino Jail Detainees’ Self-Harming Behavior: A Grounded Theory Explortion - Clemente-Faustino, Julie Ann (The prison journal, 2023)
This grounded theory exploration aims to advance a theory that explains the development of self harming behavior (SHB) among a select group of Filipino jail detainees. Using the Classical Glaserian Grounded Theory procedure, a novel process that describes Filipino Detainees’ Phases of Self Harming Behavior (gravitational, transformational, interventional and dispositional) emerged. Findings from this inquiry may serve as bases for policy-making and intervention programs that inform the triggers and preventative factors associated with SHB in the penal setting. These may further raise awareness of forensic mental health and human rights violations among detainees in flawed justice systems in low-to-middle income countries (LMICs).